HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR PADA LANSIA DI RW 09 SARDONOHARJO, NGAGLIK, SLEMAN, YOGYAKARTA - Aprianingsih, Paulina Rias; Mahayanti, Agnes; Aryu P, Scholastika Fina (STIKes Kharisma Persada, 2024)
ABSTRACTSleep quality is a measure of a person to be able to start sleeping and to maintain sleep, the quality of a person's sleep can be described from the length of sleep time, and complaints felt during sleep or after waking up. Physical activity will make the body tired so that the body produces DIPS protein and makes sleep quality good. This study aims to analyze the relationship between physical activity and sleep quality in the elderly in RW 09 Sardonoharjo, Ngaglik, Sleman, Yogyakarta with a total of 72 elderly. The sample used was 60 respondents, taken with a sampling technique, namely purposive sampling. Inclusion criteria with elderly who are willing to become respondents and have MMSE scores of 25-30 (normal cognitive). Exclusion criteria are elderly who move, elderly with physical limitations (deaf, speech, blind), elderly who have physical weakness with B-G value dependence determined by the Katz index. Instruments used PASE, and PSQI. Data analysis using SPSS version 23 with univariate statistical tests of percentage and biavariate using Spearman rho. The characteristics of respondents are age, gender, employment status, MMSE score, and Katz index. The conclusion obtained from the p-value 0.042 <0.05 means that there is a significant relationship between physical activity and sleep quality in the elderly in RW 09, Sardonoharjo, Ngaglik, Sleman, Yogyakarta. Conclusion The characteristics of the elderly are mostly (98%) aged 60-74 years, the physical activity of the elderly is less, namely most (73.3%) respondents, most (70%) respondents have poor sleep quality. Suggestions for cadres to be able to increase knowledge related to the importance of physical activity for health and the quality of elderly sleep. Suggestions for cadres to be able to increase knowledge related to the importance of physical activity for health and the quality of elderly sleep. Suggestions for the nursing field the results of this study are used as material for gerontic nursing service practice, improving the health of the elderly, examining more deeply related to sleep quality. For future researchers, they can analyze factors that affect physical activity and the quality of elderly sleep. ABSTRAKKualitas tidur merupakan ukuran sesorang untuk dapat memulai tidur dan untuk mempertahankan tidur, kualitas tidur seseorang dapat digambarkan dari lama waktu tidur, dan keluhan yang dirasakan saat tidur ataupun setelah bangun tidur. Aktivitas fisik akan membuat tubuh kelelahan sehingga tubuh menghasilkan protein DIPS.dan membuat kulaitas tidur menjadi baik. Penelitian ini bertujuan untuk menganalisis hubungan aktivitas fisik dengan kualitas tidur pada lansia di RW 09 Sardonoharjo, Ngaglik, Sleman, Yogyakarta dengan populasi lansia yaitu 72 lansia. Sampel yang digunakan sejumlah 60 responden, menggunakan teknik sampling yaitu purposive sampling.Kriteria inklusi lansia berkenan menjadi responden dan memiliki nilai MMSE 25-30 (kognitif normal). Kriteria eksklusi yaitu lansia berpindah tempat tinggal, lansia berketerbatasan fisik (tuna rungu, wicara, tunanetra), nilai B-G indeks Katz lansia. Instrumen yang digunakan PASE, dan PSQI. Analisis data menggunakan SPSS versi 23 dengan uji statistic univariat presentase dan biavariat menggunakan Spearman rho. Karakteristik responden yaitu, usia, jenis kelamin, nilai MMSE, dan indeks Katz. Kesimpulan terdapat hubungan yang signifikan antara aktivitas fisik dengan kualitas tidur pada lansia di RW 09, Sardonoharjo, Ngaglik, Sleman, Yogyakarta dengan p-value 0.042<0.05. Karakteristik lansia sebagian besar (98%) berusia 60-74 tahun, aktivitas fisik lansia kurang yaitu sebagian besar (73,3%) responden, sebagian besar (70%) responden memiliki kualitas tidur buruk. Saran bagi kader mampu meningkatkan pengetahuan pentingnya aktivitas fisik untuk kesehatan dan kualitas tidur lansia. Saran bagi bidang keperawatan hasil penelitian ini digunakan sebagai bahan praktik pelayanan keperawatan gerontik, meningkatkan kesehatan lansia, mengkaji lebih dalam kualitas tidur. Bagi peneliti selanjutnya dapat menganalisis faktor yang mempengaruhi aktivitas fisik dan kualitas tidur lansia.